Numerical simulation on foam stability and electrokinetic potential during foam injection - Alpandi, Amni Haslinda (2019)
Numerical models in petroleum reservoir simulation are valuable tools to visualize the pattern of reservoir fluid flow and to estimate production oil. Modelling enhanced oil recovery (EOR) processes requires a complex mathematical model to integrate multiphase flow and electrokinetic phenomena. There have been limited studies done in combining foam stability and electrokinetics by using simulation tools. This study aims to build and integrate a numerical model of foam progression and electrokinetic behaviour in foam injection process. This model was built using COMSOL Multiphysics 5.3 software to investigate fluid flow profiles in free liquid films stabilised by anionic surfactant, simulate foam progression and electrokinetic measurement with reasonable accuracy. Validation of the numerical model was done using finite element method. Several recent lab and simulation works were compared with this numerical simulation result to fill the gap in this research area. Hence, the relationship between stability of foam and the associated streaming potential signals was obtained. The finding shows that the algorithms suitable for this foam injection case are continuity equation, conservation of species transport, Navier Stokes equations and electric current conservation. Based on the comparison, this simulation study has high level of similarity with previous experimental and simulation works. Therefore, the effectiveness of the EOR in terms of foam stability can be monitored in real time.http://dms.library.utm.my:8080/vital/access/manager/Repository/vital:131608